Design and validation of problem-based learning student worksheets for Pancasila and Civic Education: A case study in junior high school - Weni Sarbaini (Pelita International Publishing, 2025)
Student worksheets (LKPD) serve as learning resources that contain a series of activities and exercises designed to facilitate and enhance students' understanding of learning materials. This study focuses on designing and validating problem-based learning (PBL) student worksheets for Pancasila and Civic Education (PPKn) to support the learning process of seventh-grade students at SMP IT Bina Insan Batang Kuis. The research follows the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection was conducted using questionnaires, and validation was carried out by three experts from the postgraduate program at Universitas Negeri Medan. The study reached the development phase, in which the feasibility of the designed LKPD was evaluated by expert validators. The validation results indicate that the content expert rated the LKPD at 90.75% (highly feasible), the language expert at 92.50% (highly feasible), and the learning design expert at 95.50% (highly feasible). These findings suggest that the developed PBL-based student worksheets are highly valid and suitable for use in Pancasila and Civic Education learning for junior high school students.